Climate change impacts on pest and beneficial insects: Challenges and management strategies for adaptation - Bahareh Rafiei (Arthropods, 2025)
Among the serious current global challenges, climate change significantly impinges on different organisms, including arthropods. Rising temperature, changing precipitation pattern and increasing levels of greenhouse gases that result in the expansion of insects' geographical distribution, increased survival, and generation rates, while the synchrony between plants and pests is disturbed. These alters are also associated with increased risk of invasive agricultural pests, increased prevalence of diseases by vector insects, and reduced effectiveness of biological control by natural enemies. Moreover, climate change enhances the invasive species risk through habitat alteration and reduction of biodiversity. Thus, all these climatic variables bring different outbreaks of certain pest species that cause critical economic damages in agriculture, influencing the reduction of safe food production globally. Adaptation to climate change means adopting strategies related to innovation mainly focused on integrated management approaches and using new monitoring technologies and prediction tools. The review will cover the impact of climate change on insect population and methods of its mitigation, contributing to sustainable food security.